Effect of bridge deck surface preparation on the consolidation and bond of UHPC overlays. (18th January 2023) - Helsel, Michelle A.; Muñoz, Jose F.; Haber, Zachary B.; De la Varga, Igor
Highlights: Bridge deck surface preparation effects on UHPC overlay consolidation and bond. UHPC rheology and consolidation affect bond of UHPC overlay. Roughness without damage promotes bond unless access to the substrate is inhibited. Tensile testing was performed for interface bond strength assessment. Surface roughness and interface microstructure were analyzed. Abstract: This investigation studies the effect of concrete substrate surface preparation methods on ultra-high performance concrete (UHPC) overlay bonds. Substrate surface roughnesses were analyzed using profile chips and a laser. After applying overlays to the substrates, direct tensile pull-off testing was performed to assess bond strength. Scanning electron microscopy was then used to observe representative interfaces. The study found that UHPC rheology and consolidation can significantly affect UHPC overlay bond with a high-amplitude roughness concrete substrate, particularly for thixotropic UHPCs. Surface retarder finishes were found to offer reasonably similar overlay bond performance to that of a hydromilled concrete substrate.